2021
DOI: 10.1097/txd.0000000000001181
|View full text |Cite
|
Sign up to set email alerts
|

Anonymous Living Liver Donation: Literature Review and Case Series Report

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…It has also been suggested that centers could partner with regional organ procurement organizations to reduce the burden of additional screening on individual programs. (9) In addition to ND-LLD, LPE is an attractive option to increase organ availability, but it is rarely practiced in the United States to date. It is estimated that 2%-17% of donors are rejected in the United States for ABO incompatibility, inadequate hepatic mass, or vascular or biliary anatomic variations (5) and LPE is a way to potentially address these incompatibilities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has also been suggested that centers could partner with regional organ procurement organizations to reduce the burden of additional screening on individual programs. (9) In addition to ND-LLD, LPE is an attractive option to increase organ availability, but it is rarely practiced in the United States to date. It is estimated that 2%-17% of donors are rejected in the United States for ABO incompatibility, inadequate hepatic mass, or vascular or biliary anatomic variations (5) and LPE is a way to potentially address these incompatibilities.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, many centers, including several in our study, prefer to use nondirected donors for pediatric recipients given that many pediatric recipients may be underserved by current allocation practices or because donors only need to donate a left lateral segment, which is a safer procedure and poses fewer risks of complications. (9,15) Standardizing a process that minimizes risk to the donor may help to alleviate some programs' concerns regarding the ethics of ND-LLD. Yet, questions remain as to whether there is a need for standardization of organ allocation or whether this is better left to the discretion of each institution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We read with great interest this recent article from the University of Virginia group titled “Anonymous Living Liver Donation: Literature Review and Case Series Report.” 1 We congratulate the authors for discussing this very important topic and highlighting the experience of 3 centers.…”
Section: Dear Professor Chapmanmentioning
confidence: 99%